A) E(0,0) B) A(0,1) C) C(-1,0) D) D(0,-1)
A) EA=1/2 B) EG=1 C) FG=1 D) EF=1
A) x2-y2=1 B) x2+y2=1 C) x+y2=1 D) x2+y=1
A) 1 cm B) 3 cm C) 2 cm D) 4 cm
A) 2 cm B) 1 cm C) 3 cm D) 4 cm
A) (x+1)2+(y+1)2=(3)2 B) (x+1)2+(y-1)2=(3)2 C) (x-1)2+(y-1)2=(3)2 D) (x+1)2+(y-1)2=(2)3
A) x2.y2=1 B) x2-y2=1 C) x2+y2=1 D) x2+y2=-1
A) Reemplazar el valor de "x" y despejar "y". B) Reemplazar el valor de "x" en la ecuación x2+y=1 y despejar "y". C) Reemplazar el valor de "x" en la ecuación x2+y2=1 y despejar "y". D) Reemplazar el valor de "x" en la ecuación x2+y2=1.
A) tan30°=1 B) cot30°=1 C) cos30°=1/2 D) sen30°=1/2
A) tanα=co/ca B) cosα=ca/h C) cotα=1/co D) senα=co/h |